CARTOGRAFIA CRITICA DEL FASCISMO ESPAÑOL: CHECAS DE MADRID DE TOMAS BORRAS - Santiañez, Nil (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay offers an outline for a critical cartography of Spanish fascism, based on the work of De Certeau and Foucault. Fully deployed, this cartography would enable us to understand the tactics and strategies of the construction of the Fascist state. Borrásʼs novel, Checas de Madrid, gives us a first approximation to fascist consciousness by reflecting on the Republican revolution as a general subversion of Madrid as social space.